ANALISIS PENGARUH PRODUK DOMESTIK BRUTO, NILAI TUKAR, DAN SOSIAL POLITIK TERHADAP NET CAPITAL INFLOW INDONESIA. - Fikriah Fikriah; Arie Prawira (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
The purpose of this study was to determine the effect of macroeconomic variables (gross domestic product, Exchange Rates, and Social Politics) to Net Capital Inflow Indonesia. This study uses multiple linear regression model. The data used in this research is secondary data in the form of annual namely from 1995 until 2013. Based on the results of the estimation can be concluded that the variable gross domestic product and the exchange rate (appreciation) associated positive and significant effect on Net Capital Inflow Indonesia, while socio-political dummy variables negatively related to net capital inflow Indonesia. To be able to increase net capital inflow Indonesia, the government needs to target economic growth in order to encourage domestic investment and maintaining political stability and security to invest in Indonesia. In addition the government also needs to maintain exchange rate stability in order to Net Capital Inflow not contracted. Although socio-political variable is not significant, domestic political stability remains a determinant of investment decisions and capital investment.